On Modern Possibilities of Research on Gas and Gas-Condensate Wells in Any Filtering Mode - Roy, Nick; Solovyov, Venyamin; Dmytrenko, Viktoriia; Savyk, Vasyl (International Journal of Engineering and Technology, 2018)
The analysis of studies examining gas and gas condensate wells in industrial practice indicates the positivity of carrying off work on the study of wells in the case of stationary filtration according to the traditional technology or technology of research in one mode actually worked out. In the case of examining high-permeable layers with nonstationary filtration, the studies are reduced to obtaining the pressure recovery curves and applying mathematical techniques for obtaining required information about the studied layers by means of  interpretating  them.It has been emphasized that it is the possible to use a new method of research and create of a methodology for interpreting the data obtained.In addition, a method is proposed for preliminary estimation of the value of initial gas reserves. It provides simplifying the calculation method by reducing the amount of output data; reduction of a considerable amount of geophysical research (one mode of research, is enough which combines the operation of the well in the mode and the closure of the well for the removal of  PBU curve). If one adds the possibility of application of the software product to these advantages, then we can state that solving task of calculating gas reserves in a wider spectrum can be optimized.The position on compliance with the limits of the technological corridor in the process of exploitation and research of wells has also been outlined. The method of its determination does not depend on what the filtration process is, that is whether it is stationary or non-stationary. It is characterized by relative simplicity and accessibility.